Challenges And Strategies For Improving Individual Taxpayer Compliance In The Digitalization Era - Rahmat Burhamzah; A. Reski Almaida Dg Macenning (Candela Edutech Indonesia, 2026)
This study aims to identify the main challenges hindering individual taxpayer compliance in the digital era and formulate strategies to overcome them. The rapid development of the digital economy has created complex new transaction models and income sources, creating difficulties for both tax authorities and taxpayers. The research method used is a literature study with a qualitative approach to analyze secondary data from scientific journals, government reports, and related publications. The analysis results indicate that the main challenges include the complexity of digital income tracking, the digital tax literacy gap among the public, data security and privacy issues, and suboptimal regulatory adaptation. As solutions, this study proposes several strategies. These strategies include simplifying digital-based tax services, utilizing big data analysis for oversight, improving tax education through digital platforms, and strengthening collaboration with third parties such as digital economy platforms. In conclusion, improving taxpayer compliance in the digital era requires an integrated approach that combines technological innovation with policies oriented towards taxpayer convenience and trust.